The way to organizational longevity - Balancing stability and change in Shinise firms - Sasaki, Innan (fi=Turun yliopisto|en=University of Turku|, 2015)
THE WAY TO ORGANIZATIONAL LONGEVITY – Balancing stability and change in Shinise firms The overall purpose of this dissertation is to investigate the secret of longevity in Shinise firms. On the basic assumption that organizational longevity is about balancing stability and change, the theoretical perspectives incorporate routine practice, organizational culture, and organizational identity. These theories explain stability and change in an organization separately and in combination. Qualitative inductive theory building was used in the study. Overall, the empirical data comprised 75 in-depth and semi-structured interviews, 137 archival materials, and observations made over 17 weeks. According to the empirical findings, longevity in Shinise firms is attributable to the internal mechanisms (Shinise tenacity, stability in motion, and emergent change) to secure a balance between stability and change, the continuing stability of the socio-cultural environment in the local community, and active interaction between organizational and local cultures. The contribution of the study to the literature on organizational longevity and the alternative theoretical approaches is first, in theorizing the mechanisms of Shinise tenacity and cross-level cultural dynamism, and second, in pointing out the critical role of: the way firms set their ultimate goal, the dynamism in culture, and the effect of history of the firm to the current business in securing longevity. KEY WORDS Change; Culture; Organizational identity; Organizational longevity; Routines; Shinise firms; Stability; Qualitative research

TIE ORGANISAATION PITKÄIKÄISYYTEEN – vakauden ja muutoksen tasapainottelu shinise-yrityksissä Tämän väitöskirjan tarkoituksena on tutkia shinise-yritysten pitkäikäisyyden salaisuutta. Väitöskirjan lähtökohtana on, että organisatorinen pitkäikäisyys perustuu vakauden ja muutoksen tasapainotteluun. Näin ollen väitöskirja pohjaa rutiinit käytäntöinä-, organisaatiokulttuurin ja organisaatioidentiteetin teorioihin, jotka selittävät niin yhdessä kuin erikseen vakautta ja muutosta organisaatioissa. Menetelmällisesti tutkimuksen lähtökohtana on laadullinen induktiivinen teorian rakentaminen. Empiirinen aineisto koostuu 75 puolistrukturoidusta tai syvähaas- tattelusta, 137 arkistodokumentista, sekä havainnoinnista 17 viikon ajanjaksolta. Empiiristen tulosten perusteella shinise-yritysten pitkäikäisyys pohjautuu kol- meen eri elementtiin: (1) yritysten sisäisiin mekanismeihin (shinise-sinnikkyys, vakaus liikkeessä ja muotoutuva muutos) vakauden ja muutoksen tasapainon turvaamiseksi; (2) paikallisen yhteisön sosio-kulttuurisen ympäristön jatkuvaan vakauteen; sekä (3) yrityskulttuurin ja paikallisen kulttuurin aktiiviseen vuoro- vaikutukseen. Väitöskirja kontribuoi organisaation pitkäikäisyyttä käsittelevään kirjallisuuteen sekä vaihtoehtoisiin teoreettisiin lähestymistapoihin kahdella tavalla: Yhtäältä, se teorisoi shinise-sinnikkyyden sekä kulttuuritasot ylittävän dynamiikan mekanismeja. Toisaalta, se osoittaa miten kriittinen rooli liiketoimin- nan pitkäikäisyyteen on (1) yritysten tavoitteiden asettamistavalla, (2) kulttuurin dynamiikalla ja (3) yrityksen historian vaikutuksella sen nykyiseen liiketoimin- taan. AVAINSANAT Muutos; Organisaatioidentiteetti; Organisaation pitkäikäisyys; Rutiinit; Shinise- yritykset; Vakaus; Laadullinen tutkimus